2019
DOI: 10.1017/ice.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate ceftriaxone use in outpatient acute respiratory infection management

Abstract: Financial support. No financial support was provided relevant to this article. Conflicts of interest. A.M. reports consulting for Becton Dickinson. S.E.C. reports consulting for Theravance and Novartis. All other authors report no conflicts of interest relevant to this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Third-generation cephalosporins, such as ceftriaxone, are broad-spectrum antibiotics and are frequently prescribed in pediatrics despite a lack of first-line indications [ 11 ]. Preserving the use of such agents to treat serious and resistant bacterial infections [ 12 ] and reducing unnecessary broad-spectrum and parenteral antibiotic use are key to optimizing treatment of infectious conditions and to minimizing the risk of antibiotic-associated adverse events and development of antibiotic resistance.…”
mentioning
confidence: 99%
“…Third-generation cephalosporins, such as ceftriaxone, are broad-spectrum antibiotics and are frequently prescribed in pediatrics despite a lack of first-line indications [ 11 ]. Preserving the use of such agents to treat serious and resistant bacterial infections [ 12 ] and reducing unnecessary broad-spectrum and parenteral antibiotic use are key to optimizing treatment of infectious conditions and to minimizing the risk of antibiotic-associated adverse events and development of antibiotic resistance.…”
mentioning
confidence: 99%
“…In a previous study performed during COVID-19 in Egypt, some of the surveyed community pharmacists reported dispensing a non-appropriate dose of ceftriaxone (Elsayed et al, 2021 ). Levofloxacin and ceftriaxone wide and irrational use before and during the pandemic in both the inpatient and the outpatient settings could have contributed to the increased antimicrobial resistance (King et al, 2019 ; Medic et al, 2023 ). Physicians accepted all of the DTC-trained clinical pharmacists-led recommendations, in line with a previous study (Malani et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%